The Development of Android-Based Open-Ended Approach Teaching Materials on Squares and Triangles - Neda Permana; Heris Hendriana; Rudy Kurniawan (IKIP Siliwangi, 2022)
In industrial revolution 4.0, education must follow and utilize information and communication technology. Android is an operating system on mobile devices, and Indonesia's most popular and widely used mobile device operating system. The Open-Ended approach is an approach in mathematics learning that provides opportunities for students to explore open problems with various strategies for solving problems. One problem that often arises in learning in schools is the study of the anchovies of each textbook varies, and the material contained in the book does not match the characteristics of the students. To realize this, the world of education needs to implement the use of e-Modules. Seeing this problem, the development of an android-based e-Module with an open-ended approach is required. Research and development with the ADDIE model is this type of research. The subjects of this study were as many as 15 middle school students in grade 8 for limited tests and 30 students for a broader test. The research aimed to produce Android-based electronic teaching materials with an open-ended approach to square and triangular materials. The resulting product is an e-Module in the form of an android package kit (APK). The result of the study concluded that the development of teaching materials with an android-based open-ended approach went well with the practicality test results obtained by 83%, which means that the teaching materials are efficient to use and got 86.6% in the effectiveness test, which means that the teaching materials developed are suitable for use.